x-intercept: Set y to 0 and solve for x:
4x - 3y - 6 = 0 becomes:
4x - (3 * 0) - 6 = 0
4x - 0 - 6 = 0
4x - 6 = 0
4x - 6 + color(red)(6) = 0 + color(red)(6)
4x - 0 = 6
4x = 6
(4x)/color(red)(4) = 6/color(red)(4)
(color(red)(cancel(color(black)(4)))x)/cancel(color(red)(4)) = 6/4
x = 3/2
The x-intercept is: x = 3/2 or (3/2, 0)
y-intercept: Set x to 0 and solve for y:
4x - 3y - 6 = 0 becomes:
(4 * 0) - 3y - 6 = 0
0 - 3y - 6 = 0
-3y - 6 = 0
-3y - 6 + color(red)(6) = 0 + color(red)(6)
-3y - 0 = 6
-3y = 6
(-3y)/color(red)(-3) = 6/color(red)(-3)
(color(red)(cancel(color(black)(-3)))y)/cancel(color(red)(-3)) = 6/-3
y = -2
The y-intercept is: y = -2 or (0, -2)